2018
DOI: 10.1007/s00167-018-4938-y
|View full text |Cite
|
Sign up to set email alerts
|

Bone-to-bone integrations were complete within 5 months after anatomical rectangular tunnel anterior cruciate ligament reconstruction using a bone–patellar tendon–bone graft

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…For anterior cruciate ligament (ACL) reconstructions, recent efforts from Japan and Europe have intended to reproduce the anatomy of the femoral ACL insertion site by using a rectangular-shaped tunnel [ 6 , 12 , 18 , 26 , 27 ]. This allows to place the tunnel aperture into the ACL footprint and reproduce the anatomy of the native ACL and its fiber insertions.…”
Section: Introductionmentioning
confidence: 99%
“…For anterior cruciate ligament (ACL) reconstructions, recent efforts from Japan and Europe have intended to reproduce the anatomy of the femoral ACL insertion site by using a rectangular-shaped tunnel [ 6 , 12 , 18 , 26 , 27 ]. This allows to place the tunnel aperture into the ACL footprint and reproduce the anatomy of the native ACL and its fiber insertions.…”
Section: Introductionmentioning
confidence: 99%
“…26 In addition, Masuda et al reported that bone-to-bone integration on the femoral and tibial sides was completed within 5 months after surgery in all of their cases. 27 Taketomi et al reported that bone plug migration in the bone tunnel was observed in only 15% of the patients, and a mean difference of 0.4 AE 0.4 mm was observed between the two time points (1 week and 1 year after surgery). 28 This result indicates that bone plug migration could not affect postoperative anterior knee stability when the BPTB graft is used.…”
Section: Discussionmentioning
confidence: 99%
“…A slice was defined to have achieved bone integration if there was bone trabeculae continuity between the bone plug and bone tunnel 14 (Fig 2). The sagittal plane on the femoral side and the coronal plane on the tibial side were investigated in this study using methods described in a previous study 11 (Fig 3). The ratio of bone integration was compared between both modalities by both surgeons.…”
Section: Radiographic Analysismentioning
confidence: 99%
“…Although the time required for tomosynthesis to evaluate bone graft integration was not established using a comparison of both modalities, we evaluated CT and tomosynthesis data at 3 months postoperatively during this study. Masuda et al 11 reported that bone grafts were 100% healed at 5 months postoperatively; however, only 50% were healed at 3 months. Therefore, a 50% integration rate seemed suitable for this study.…”
Section: Radiographic Analysismentioning
confidence: 99%
See 1 more Smart Citation